Traumatic rupture of the oesophagus and stomach - Craddock, D. R. (1968)
Thirty-nine cases of traumatic perforation of the oesophagus or stomach have been studied. Thirty-two of the perforations followed oesphagoscopy, five were `spontaneous,' and two were due to damage by a foreign body. Eight of the perforations occurred in the cervical oesophagus, 22 in the thoracic portion, and nine were in either the abdominal oesophagus or the stomach. Treatment was of two types—either operative closure of the perforation or a conservative routine of intravenous fluids, parenteral antibiotics, and cessation of oral feeding. In some patients treated conservatively, drainage procedures were also carried out. Five patients with terminal carcinoma, in whom oesophageal intubation after prolonged dysphagia caused perforation, had no treatment apart from analgesics and sedatives. Several of the patients treated by surgical closure had a concurrent definitive operation (resection of carcinoma in four cases and myotomy for achalasia in two cases). Fourteen of the 21 patients treated by repair or resection of the perforation survived. Ten of the 13 treated conservatively also survived. The good results of conservative treatment for cervical perforations appear to make it the treatment of choice. Only an occasional case of thoracic perforation is suitable for conservative treatment, and as a general rule perforations in this area and in the peritoneal cavity should be treated surgically.